2004
DOI: 10.1111/j.0022-202x.2004.22413.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Size as the Main Determinant of Solute Maximum Flux Across the Skin

Abstract: One of the most important determinants of dermatological and systemic penetration after topical application is the delivery or flux of solutes into or through the skin. The maximum dose of solute able to be delivered over a given period of time and area of application is defined by its maximum flux (J(max), mol per cm(2) per h) from a given vehicle. In this work, J(max) values from aqueous solution across human skin were acquired or estimated from experimental data and correlated with solute physicochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 76 publications
6
160
1
Order By: Relevance
“…According to the flux value of ion-pair complexes and their physicochemical properties listed in Table III, the skin permeability of ESP altered due to the altered physicochemical properties of ESP by forming ion-pair complexes with organic acids. Many previous studies about skin permeation reported that the physicochemical properties of drugs including log K o/w and MW could affect the skin permeability of drugs (20,21). Ma et al and Tan et al also found that the flux of drug was influenced by the pK a of counter-ions (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…According to the flux value of ion-pair complexes and their physicochemical properties listed in Table III, the skin permeability of ESP altered due to the altered physicochemical properties of ESP by forming ion-pair complexes with organic acids. Many previous studies about skin permeation reported that the physicochemical properties of drugs including log K o/w and MW could affect the skin permeability of drugs (20,21). Ma et al and Tan et al also found that the flux of drug was influenced by the pK a of counter-ions (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8][9][10][11] The most recognised and applied QSPR to predict the skin permeability coefficient (k p ) is that developed by Potts and Guy in 1992 (Eq. 2).…”
Section: Skin Permeabilitymentioning
confidence: 99%
“…the route of entry into the viable skin is via passive diffusion through the stratum corneum. Depending on lipophilicity and molecular weight, the rate and route of transport across stratum corneum varies, predominating through either the lipid bilayers, corneocytes or via appendages such as sweat ducts and hair follicles (Potts and Guy, 1992;Mitragotri, 2003;Magnusson et al, 2004). Once present in the viable skin, the ingredient will distribute between extra-and intra-cellular space, where there is the potential for both phase I (activation of pro-haptens) and phase II (predominantly clearing) metabolism (Gibbs et al, 2007;Hagvall et al, 2008;van Eijl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%